Opportunities with visualisation linked with virtualised data: a case study. (15th May 2019) - Prakash, Mishra Jyoti; Kumar, Mishra Sambit; Kumar, Mishra Anil
The concept of virtualisation along with the physical objects and IP address for internet connectivity may be a big challenge in the present society. It may refer to the numerous physical devices around the world connected with internet for collecting and sharing data. Specifically, the technology associated with internet of things (IoT) may be viewed as the network of physical objects embedded along with connectivity to share and exchange data linked among the physical and cyber space. Sometimes also it may create opportunities for direct integration between the physical world and computer- based systems and leads to economic benefits. It may be thought of connected devices to transfer data among one another in order to optimise the performance automatically and quite a major challenge. It has been proposed to analyse the opportunities and performance associated with virtualised data to simplify and strengthen human activities as well as expertise.